Sizing filoneanos deposits by tectonic approach: Take the hand veins example - Ancash Region - Vela Velásquez, Churchill (2012)
The mineralization of the Andes is a result of the deformation of the Nazca and South American plates, related to geological structures as a result of Andean deformation, whose study of the geometry of the mineralized bodies depend largely tectonic good knowledge reservoir area, being necessary to apply special methods and tectonic microtectónicos that lead to determine the tectonic model of a region and its consequent relationship with the mineralized structures. For the application of the method of determining the geometry of filoneanos sites, it is taking the example of the veins of the Mining Corporation Take Hand, located on the axis of the Cordillera Blanca Huascaran Park, Province of Carhuaz, Ancash, where we make a tectonic study and complete microtectónico, to determine the extent of the veins. The method consists of first determining the geological macrostructure through regional tectonic maps, prepared to locate and relate to the area of the deposits within the regional tectonic context . Then using microtectónicos methods used in the analysis of tectonic fractures and folds, created by Professor Maurice Mattauer at the University of Montpellier - France and adapted by the author of this publication to the Central Andes of Peru , prepares the detailed tectonic mapping the area of mining interest in the study, thus obtaining the surface tectonic model made ​​compatible with the specified macrotectónica . Next, using the same methods used microtectónicos surface structure is determined ore bodies inside the mine , correlated surface structures recognized with inner mine structures , thus obtaining a complete tectonic model for projecting both horizontal extent and depth studied mineralized structures .